Phylogenies with Corroboration Assessment - Faith, Daniel P; Köhler, Frank; Puslednik, Louise; Ballard, J. W. O. (Zootaxa, 2011)
Mooi & Gill (2010) argued that careful character study and well-understood synapomorphies do not have the strong role that they deserve as the basis for evidence in phylogenetics. We agree, but suggest that the problem is even greater. Not only character synapomorphies, but also other forms of phylogenetic evidence, typically do not receive the critical assessment that would support phylogenetic inference. In this paper, our goal is to not simply to highlight problems but to suggest solutions. We will suggest that a stronger role for corroboration assessment in systematics could overcome these problems in phylogenetic inference.